Social Dimensions of Health: Ritual Practice, Moral Orders, and Worlds of Meaning in Brazilian Candomblé and Umbanda Temples. (29th September 2020) - Markus, Wiencke
Abstract: In Western medicine the interpretation prevails that mental illness is a psychological and/or biological disorder. Most important concepts in health psychology, such as sense of coherence, self‐efficacy, hope, or dispositional optimism are all very cognition and individual centered. In this individualized perspective, mental illness is constructed in such a way that it can be treated in a dyadic doctor–patient or therapist–patient relationship with the help of drugs or therapeutic techniques. In this article, I would like to develop a contrasting social construction of mental illness. In Umbanda and Candomblé temples in Brazil, what is interpreted in the Western model as illness is understood as a "spiritual problem." Here, the individual is constructed in relationship to the community, and individual health and healing is footed in moral‐spiritual orders. In presenting the details of my investigation, I will apply Grawe's common factors as a foil for developing the link between mental illness and its social context.